Determinants of Health Outcomes of Patients Presenting with Massive Traumatic Bleeding in the Emergency Department in Selected Hospitals in Kiambu County, Kenya - Odaro, Anne Edith; Odongo, Alfred Owino; Njuguna, Josphat (International Journal of Health Sciences, 2024)
Purpose: The study sought to identify the determinants of the health outcomes of patients presenting with massive traumatic bleeding in the emergency department of selected hospitals in Kiambu County, Kenya. Methods: The research employed an analytical cross-sectional study design, utilizing quantitative data. Data was collected using a questionnaire, an observation checklist, and extraction of secondary data from patient records. A census sampling was done. The collected data underwent analysis using IBM SPSS version 26. Simple linear regression and multiple logistic regression analysis was used to analyze the data. Results: Regarding the health outcomes of patients presenting with massive traumatic bleeding, three outcomes were observed: 68.39% of the patients were discharged in fair general condition (FGC), 21.70% were referred and 9.90% were deceased. The experience of the healthcare workers, 11.6% of the variability of the health outcome of the patient is explained by experience of healthcare workers (p-value = 0.0138). Comparing the health outcomes in the two facilities, there was no difference in health outcome (p<0.001). According to the multinomial logistic regression the results indicate that age is a significant predictor of the deceased outcome (B=0.064, p=0.014). Therefore, age is the most significant predictor of the health outcomes of patients presenting with massive traumatic bleeding. Unique Contribution to Theory, Policy and Practice: To reduce poor health outcomes of pediatric and geriatric patients, it is recommended that a specific area in the emergency department should be set aside for the trauma patients in these age categories. Due to adding special areas in the emergency department, more staff and resources will need to be allocated to the emergency department.